Cloud technology module for aggregation of survey data of housing and buildings in coastal villages as per IS:15499 towards cyclone disaster mitigation - Sasikala, K.; Harikrishna, P.; Selvi, S. Thamarai (Journal of Structural Engineering, 2024)
With the help of advanced forecasting tools and warning systems, the loss of life could be reduced significantly during the recent very severe cyclonic storms “Phailin” (2013) and “Hudhud” (2014), which crossed the east coast of India, in comparison to the previous cyclones of similar intensity. However, the damage to housing/buildings in Indian coastal villages, in proportion to the intensity of the cyclone, is observed to be continuing. CSIR-Structural Engineering Research Centre (CSIR-SERC), Chennai has been carrying out various studies/activities for the mitigation of damage to housing/buildings in coastal villages due to cyclones for the past few decades. Earlier, CSIR-SERC has evolved survey data sheets to collect structural details of housing/buildings for cyclone damage mitigation. Using these data sheets, survey of housing was carried out in a limited number of coastal villages to identify commonly adopted materials and construction practices. Based on which cost-effective retrofit measures for improved resistance to cyclonic winds have been derived by conducting tests at CSIR-SERC. Subsequently, some of these indigenously evolved survey data sheets were standardized by Bureau of Indian Standards (BIS) in 2004 (IS: 15499). In present study, as part of the development of a Decision Support System (DSS) to assess the cyclone vulnerability of housing/buildings in Indian coastal villages, a web service module using the latest ‘CLOUD TECHNOLOGY’ has been developed for the automated aggregation of survey data of housing and buildings as per the standardized Proformae from numerous villages, which are geographically located in different Taluks/Districts/States of Indian Coastal Region. This paper highlights the relevant features of the web service module developed for the aggregation of survey data from Indian coastal regions towards cyclone disaster mitigation.